Coping strategies and locus of control in childhood leukemia: a multi-center research - Concetta Polizzi; Valentina Fontana; Giovanna Perricone; Paolo D'Angelo; Momcilo Jankovic; Calogero Taormina; Francesca Nichelli; Sofia Burgio (MDPI AG, 2015)
Acute lymphoblastic leukemia (ALL) is a very distressing experience for children and requires a special effort of adjustment. Therefore, it seems to be crucial to explore coping resources for the experienced risk condition. In this sense, the study focuses on coping strategies and locus of control in children with ALL during the treatment phase, and on their possible relation. The correlation between children and maternal coping strategies is also investigated. The participants involved were an experimental group of 40 children with ALL and their mothers, and 30 healthy children as the control group. The tools used were: the Child Behavioral Style Scale and the Monitor-Blunter Style Scale to assess the coping strategies of children and mothers; the locus of Control Scale for Children to analyze the children's perception of controlling the events. Both children with ALL and their mothers resorted to monitoring coping strategies with a statistically significant rate of occurrence (children: M=17.8, SD=3.8; mothers: M=10.48, SD=3.4). The data concerning the locus of control show this tendency towards internal causes (M=53.1, SD=4.7). There were statistically significant correlations between monitoring coping strategies and external locus of control (r=0.400, P<0.05). The results gained from the control group are almost equivalent. The outcomes show several interesting resources of the psychological functioning of children as well as of their mothers.